Experimental Validation of a Novel PI Speed Controller for AC Motor Drives With Improved Transient Performances - Errouissi, R.; Al-Durra, A.; Muyeen, S.M. (Institute of Electrical and Electronics Engineers, 2017)
A proportional-integral (PI) controller is the most frequently used control technique for adjustable speed-motor drives. The main advantage of a PI controller is its ability to ensure zero steady-state error under low-frequency disturbances and model uncertainties as long as the closed-loop system is stable. However, the transient performances, under a PI regulator, are highly dependent on the machine parameters, the external disturbances, and the input constraints. This brief proposes the design process of a novel PI speed controller that is capable of preserving almost the nominal transient performance under the parameter variation and external disturbances such as the load torque. The controller also suppresses the effect of input saturation that may occur because of the armature current limitation. Simulation and experimental tests are carried out to verify the validity of the proposed design process. The results revealed that the proposed PI controller is effective regarding nominal performance recovery and input constraints handling.